(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
One of the top priorities in world linguistics is the linguistic approach to the study of linguistic units with national and cultural content. Another is the analysis of the national spirit of peoples reflected in world languages and the identification of ethno cultural features of linguistic expression in human relations. It should be mentioned that the main emphasis is on the psycholinguistic, linguocognitive, lingvoculturological, and sociolinguistic nature of language as well as how it functions in the lives of various peoples.